A Meta-Analysis on the Risk Factors of Low Back Pain in Health Workers - Akbar, Muh. Syaiful; Rahardjo, Setyo Sri; Indarto, Dono (Journal of Epidemiology and Public Health, 2020)
Background: Low back pain is a common prob